Improved awareness of physical activities is associated with a gain of fitness and a stable body weight in breast cancer patients during the first year of antineoplastic therapy: the BEGYN-1 study - Zemlin, Cosima; Schleicher, Julia Theresa; Altmayer, Laura; Stuhlert, Caroline; Wörmann, Carolin; Lang, Marina; Scherer, Laura-Sophie; Thul, Ida Clara; Spenner, Lisanne Sophie; Simon, Jana Alisa; Wind, Alina; Kaiser, Elisabeth; et al. (Frontiers in Oncology, 2023)
Background: Breast cancer is the most frequent cancer in women. Reduced physical activity and overweight are associated with poor prognosis. Breast cancer patients have a high risk to gain weight, lose muscle mass and reduce physical activity during therapy. Concepts are urgently needed to motivate patients to engage in physical activity. Methods: 110 non-metastatic breast cancer patients were included in the prospective observational BEGYN-1 study. Physiological parameters and body composition were measured before the start of therapy and then quarterly for one year. Patients used a fitness tracker and documented their physical activity in a diary throughout the study. Results: Although the patients were not offered any guided exercise, and despite the restrictions during the COVID-19 pandemic, they increased their physical activity (metabolic equivalent of task (MET) -minutes): p<0.001), physical fitness (decreasing resting heart rate: p=0.001) and did not gain weight (median - 0.4kg) over the course of the study. Conclusion: Improved awareness of physical activity is associated with an increase in physical activity, fitness, and a stable weight during the first year of therapy in breast cancer patients. Counselling at diagnosis should motivate patients to engage in physical activity, wear a fitness tracker and document activities.